Eduardo Mayobre. Venezuela, 1948-1958. La dictadura militar. Caracas: Fundación Rómulo Betancourt, 2013 - Castillo Herrera, Luis Fernando (Historia Caribe, 2013)
Eduardo Mayobre. Venezuela, 1948-1958. La dictadura militar. Caracas: Fundación Rómulo Betancourt, 2013